Организация обучения чтению специальных текстов в системе профессионально-ориентированного обучения иностранным языкам - Садакбаева, А.А. (My University, 2016)
The focus of the article is directed to the developing professionally-oriented reading as the basic of language learning process in non-linguistic higher education institution. The author offers some types of reading and ways of working on the text.
Keywords: professionally-oriented reading; authenticity; teaching; types of reading; professional terms